Pemanfaatan Limbah Botol Plastik Menjadi bahan Baku (Filamen) 3D Printer dengan menggunakan Alat Pultrusion Untuk Masyarakat PKBM: Utilization of Plastic Waste for 3D Printing Filament Production Using Pultrusion in Community Learning Centers - Ivanto, Muhammad; Lubis, Gita Suryani; Prima, Febri; Hafid, Aariz; Sahrudin, Sahrudin; Manhargo, David (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The Community Learning Center (PKBM) is a non-formal education unit in Indonesia established by the community and functioning as a hub for education, training, and community empowerment services. PKBMs provide an alternative pathway for individuals who are unable to access formal education. One such institution in West Kalimantan is PKBM Adam, located in Kubu Raya Regency.  In daily activities, both teachers and students commonly bring bottled mineral water, leading to increased plastic waste. The plastic bottles eventually pile up, creating environmental concerns and diminishing the aesthetic value of the surrounding area. To address this issue, it is essential to equip teachers with the knowledge and skills to recycle plastic waste into filament, which can serve as raw material for 3D printing.  As part of this collaboration, university lecturers designed and developed a pultrusion machine and a 3D printer. The program was implemented through several stages, including partner site visits, group discussions and socialization sessions, equipment development, and hands-on training for teachers and students on how to operate the tools provided. Furthermore, pre-tests and post-tests were conducted to assess participants' comprehension of the activities.  The results demonstrated an 80% improvement in teachers' and students' understanding. After the training sessions, teachers and students were able to operate all of the provided equipment effectively. Moreover, the implementation of this program successfully reduced plastic bottle waste within the PKBM Adam environment.